Pengaruh Struktur Modal Dan Likuiditas Terhadap Return Saham Dengan Moderasi Ukuran Perusahaan - Yahya, Husaini; Hermuningsih, Sri; Sari, Pristin Prima (Jambura Economic Education Journal, 2026)
This study “aims to examine and analyze the effect of capital structure and liquidity on stock returns, with firm size as a moderating variable. The study population comprised manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was obtained through purposive sampling, resulting in 45 companies meeting the criteria. The analytical method used was Moderated Regression Analysis (MRA) with the help of SPSS version 27. The results show that capital structure has a negative and significant effect on stock returns, liquidity has a negative and significant effect on stock returns, and firm size has been shown to moderate the effect of capital structure and liquidity on stock returns. These findings indicate that decisions regarding capital structure and liquidity levels must consider firm size, as the larger the firm size, the stronger its role in influencing the relationship between these variables.”